Scientific Testimony Terhadap Hukuman Mati Bagi Pelaku Tindak Pidana Narkotika - Cardio S. Butar-Butar; Alpi Sahari; Surya Perdana (Mahesa Research Center, 2020)
The rise of narcotics circulation in recent years, has caused many losses not only economic losses but the loss of a generation of people who have lost common sense to become victims of life, even though in a very productive age. Based on this condition, the legal policy taken by the government by making maximum legal sanctions for drug dealers and drug dealers with a maximum sentence of life or death sentence. This writing aims to examine the position and function of scientific testimony on the death penalty for narcotics offenders and the perspective of North Sumatra BNN and North Sumatra Regional Police on scientific testimony on the death penalty for narcotics offenders. The results of this study indicate that the use of scientific testimony in criminal cases will scientifically reveal narcotics criminal cases, so that it can be seen what articles can be applied in narcotics crime cases, that the position and function of scientific testimony against capital punishment for narcotic offenders is as a tool or means to supplement other evidence whether a suspect is indeed eligible for a death sentence or not and also whether or not a recommendation from the results of scientific testimony can change the law enforcement authorities not to impose the death penalty for narcotics offenders depending, whether the investigator or the investigator is willing to use information from the letter of the results.